2018
DOI: 10.1108/hff-06-2018-0337
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of mixed convection of different nanofluids in concentric annulus

Abstract: Purpose This study aims to investigate the numerical analysis of mixed convection within the horizontal annulus in the presence of water-based fluid with nanoparticles of aluminum oxide, copper, silver and titanium oxide. Numerical solution is performed using a finite-volume method based on the SIMPLE algorithm, and the discretization of the equations is generally of the second order. Inner and outer cylinders have a constant temperature, and the inner cylinder temperature is higher than the outer one. The two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In laminar flow through a hexagonal cross‐sectional duct with constant wall temperature, entropy generation is studied by Oztop et al 35 Further study on entropy generation can be seen through previous studies 36–42 . Some of the relevant and recent numerical studies on flow with heat transfer analysis for various thermodynamic systems are given 43–65 …”
Section: Introductionmentioning
confidence: 99%
“…In laminar flow through a hexagonal cross‐sectional duct with constant wall temperature, entropy generation is studied by Oztop et al 35 Further study on entropy generation can be seen through previous studies 36–42 . Some of the relevant and recent numerical studies on flow with heat transfer analysis for various thermodynamic systems are given 43–65 …”
Section: Introductionmentioning
confidence: 99%
“…Enclosures also have different applications in a wide range of industries and equipment, such as cooling [23,24], Heating, Ventilation, and Air Conditioning (HVAC) [25], nuclear power [26], heat exchangers [27,28], renewable energies [29], etc.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the rotation direction of the hot and cold cylinders has a significant impact on heat transfer rate. Abedini et al (2019) investigated mixed convective heat transfer of nanofluid in the horizontal annulus. Their results indicate that the heat transfer enhances as the Rayleigh and Richardson numbers increase.…”
Section: Introductionmentioning
confidence: 99%